Synergy of Electrostatic and π–π Interactions in the Realization of Nanoscale Artificial Photosynthetic Model Systems - Anaya-Plaza, Eduardo; Joseph, Jan; Bauroth, Stefan; Wagner, Maximilian; Dolle, Christian; Sekita, Michael; Gröhn, Franziska; Spiecker, Erdmann; Clark, Timothy; de la Escosura, Andrés; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie International Edition, 2020)
In the scientific race to build up photoactive electron donor-acceptor systems with increasing efficiencies, little is known about the interplay of their building blocks when integrated into supramolecular nanoscale arrays, particularly in aqueous environments. Here, we describe an aqueous donor-acceptor ensemble whose emergence as a nanoscale material renders it remarkably stable and efficient. We have focused on a tetracationic zinc phthalocyanine (ZnPc) featuring pyrenes, which shows an unprecedented mode of aggregation, driven by subtle cooperation between electrostatic and π–π interactions. Our studies demonstrate monocrystalline growth in solution and a symmetry-breaking intermolecular charge transfer between adjacent ZnPcs upon photoexcitation. Immobilizing a negatively charged fullerene (C60) as electron acceptor onto the monocrystalline ZnPc assemblies was found to enhance the overall stability, and to suppress the energy-wasting charge recombination found in the absence of C60. Overall, the resulting artificial photosynthetic model system exhibits a high degree of preorganization, which facilitates efficient charge separation and subsequent charge transport.
CRIS-Team Scopus Importer:2020-09-11
Keywords: artificial photosynthesis; fullerenes; nanoscale self-assembly; phthalocyanines